The Design and Construction of a Domestic Microcontroller based Dangerous Gas Detector (International Journal of Scientific Research and Management (IJSRM), 2018)
Abstract - Fire hazards are becoming rampant in recent years and takes toll on lives and properties. This fatal inferno has been trailed to the leakages of gas in industries and household especially. LPG is highly inflammable and can burn even at some distance from the source of leakage. Various accidents resulting could be as a result of a poor-quality rubber tube or when the regulator is not turned off and careless handling of the LPG cylinders. The supply of gas from the regulator to the burner is on even after the regulator is switched off. By accident, if the knob is turned on it results in gas leaks. The adverse effect and bad experiences of victim of gas leakages inform the pursuit of this research work. This paper describes a microcontroller-based system that is designed with cheap electronic component to detect and alert the domestic environment when LPG leakage is detected. The system is easy to deploy and void of complex configurations and installation. This work curtails injuries and losses caused by explosions due to gas leakages and improve safety of life and property while using domestic cooking gas. Key Words: LPG, Regulators, Burner, Microcontroller-based, Leakage, explosion.